Evaluation of the efficiency of coffee mucilage as an organic coagulant for the removal of turbidity, considering the optimal pH and optimal dosage - Bello Segura, Gibrán; Banda Santamaría, Santiago; García Villanueva, Luis Antonio (Gibrán Bello Segura, Santiago Banda Santamaría, Luis Antonio García Villanueva., 2023)
The urgent need to satisfy the demand of water for human use and consumption with a sustainable approach makes it necessary to look for new alternatives for the removal of turbidity in this environmental matrix. Therefore, the present work aims to evaluate the efficiency of coffee mucilage as an organic coagulant,for turbidity removal. Considering the pH and optimal dose. Jar tests were conducted, and the concentration of coffee mucilage was determined using samples collected from different extraction methods. The optimal pH for turbidity removal was found to be 11 and 12 with the optimal dose of 10 and 20 ml of coffee mucilage as coagulant. It is proved that coffee mucilage organic coagulant is an effective and viable option for turbidity removal in synthetic water, achieving removal efficiencies of 91.38% at pH 12 and 90.99% at pH 11.
This study explores using coffee mucilage as an organic coagulant for turbidity removal in water. Optimal turbidity removal was achieved at pH levels 11 and 12, with doses of 10 and 20 ml, reaching efficiencies of over 90%. The findings suggest that coffee mucilage is an effective and sustainable option for water treatment.
Keywords: Coffee mucilage; Turbidity removal; Organic coagulant; Water treatment; Dosage and pH